A comparative study on the tibial morphology among several populations in ancient East Asia - Zhang, Qun (2022)
Human skeletal morphology is a dynamic system affected by both physiological and environmental factors, due to the functional adaptation and remodeling responses of bones. To further explore the adaptation of bone to the environment and the consequent subsistence strategies determined by the diverse natural contexts in the Anthropocene, this study presents a comparative study on the tibiae of seven ancient populations located in different regions of East Asia. Through the analysis of the tibial shaft morphology, a comparative analysis between the populations and genders was conducted to evaluate the differences in external morphology and sexual division of labor. The cnemic indices of the tibial shaft were selected to quantify the external shape. Results showed that different populations had different tibial morphology. Among males, those of Jinggouzi had the flattest tibia while those of Changle had the widest tibia. Among the females, females of Hanben had the flattest tibia, whereas tibia from females of Shiqiao, Changle, and Yinxu were among the widest. The sexual dimorphism was relatively larger in Shiqiao and Jinggouzi and smaller in Tuchengzi and Changle. Through a combination of previous archaeological findings, historical records, and ethnography of the aboriginal Taiwanese, it is concluded that the terrain and ecological environments laid basis for varied subsistence strategies. In addition, the mobility and social labor division under a particular subsistence strategy further contributed to the adaptation of the lower limb morphology to its context. The comparative analysis provides further insight on habitual activities, terrestrial mobility patterns, and subsistence strategies of the populations, which lived in different environmental contexts during the Bronze Age and early Iron Age, thus demonstrating the diverse interactions between human populations and natural environment in the Anthropocene.